Phytoremediation potential of two species Brassica juncea and Brassica carinata in soils contaminated by cadmium - Zahra Soleimannejad; Ahmad Abdolzadeh; Hamidreza Sadeghipour (علوم محیطی)
Introduction: Heavy metals are one of the most important environmental pollutants that have been highly regarded in recent decades. The accumulation of elements in the soil, especially in agricultural land, has been gradual and the concentration of heavy elements can reach to the level that threaten human food security. Among heavy metals, cadmium is considered as one of the most dangerous elements due to its high mobility in biological systems, high toxicity, high solubility in water and rapid absorption by the root system of many plant species. Therefore, in this research, the growth, accumulation and phytoremediation potential of cadmium in two species Ethiopian mustard (Brassica carinata) and Hindi mustard (Brassica juncea) is studied. Materials and methods: Plants in contaminated soils with concentrations of 0, 75 and 150 mg kg-1 of cadmium were grown in greenhouse and harvested after 7 weeks  to measure some growth characteristics.Results and discussion: The results showed that cadmium treatments had no significant effect on growth traits and chlorophyll content of two plant in compared with control. Both plant showed high stress tolerance index and low stress tolerance to cadmium. With increasing cadmium concentration in soil, cadmium concentrations in root and shoot of both plants B. carinata and B. juncea significantly increased. The translocation factor of B. juncea was about 70% higher than B. carinata.The highest translocation factor was observed in the treatment of 75 mg kg-1 of cadmium in B. juncea. Conclusion: The comparison of two plants of B. carinata and B. juncea showed that both species are able to tolerate and accumulate cadmium, but translocation factor, uptake and accumulation of cadmium in plant B. juncea was more than B. carinata. So it seems B. juncea had better performance for use in phytoremediation process.